Shaping of the Stoicheiometry Concept in Secondary Education: Greek Minor Urban Area High Schools (Journal of Education and Development, 2023)
A study is carried out by means of distributing a pair of questionnaires to secondary education students in minor urban areas of Northern Greece. The content of the questions is related to the concept of stoicheiometry (Note 1) as it is presented in the textbooks and described in the Greek chemistry curriculum for secondary education. The two questionnaires were distributed in the beginning and in towards the end of the school year with the scope of mapping the degree of assimilation of the stoicheiometry related concepts by the students. The concept is not introduced to a considerable extent in junior high-school while it is among the main topics addressed in the second grade of senior high-school, when Organic Chemistry is explicitly discussed. The target group therefore, was students of second grade of senior high-schools. The first questionnaire, therefore, serves as exploratory in the determination of the starting point of overall understanding of chemical concepts by the students. The validity of the questionnaires and their efficiency in fulfilling the scope of the current research was carried out by the application of certain post-statistical indices with the final goal being their utilization as a diagnostic tool for probing student understanding of chemical concepts.